Project title: The Morbidity associated with Painful Neuropathy in HIV-infected subjects Anti-Retroviral Therapies: An assessment of self-management stratergies - Ismail, Dr M (Department of Medicine, 2014)
Objective: To establish the frequency of anti-retroviral treatment (ART)-related distal sensory polyneuropathy in a community-based clinic. To identify the self-management strategies these subjects are using to cope with their pain, and the possible impact on therapeutic management. Methods: A cross-sectional analysis was done of the patients attending the ART clinic at Woodstock Community Health Centre (CHC). During the three-month study period, 123 patients on anti-retroviral therapy were asked to answer the questionnaire and those who had painful feet, were then asked to complete questions about health- seeking behaviors. All participants were asked to complete questions about their health status and all were assessed with the Brief Peripheral Neuropathy Screen (BPNS). Based on the finding of the BPNS, subjects were divided into those with symptomatic distal sensory polyneuropathy (SDSP) and those without. SDSP was defined as the presence of any of the neuropathic symptoms in addition to one of the following; either reduced or absent ankle reflexes or abnormal vibration sense of 10 seconds at the great toes. Further data was obtained from patients by asking them to answer questions with regard to quality of life (QOL) as well depression. Results: Almost one third of patients were diagnosed with SDSP. Of those affected, 73% had significant pain ranging from moderate to severe intensity. Many of these patients were using self-management strategies, such as paracetamol (68%), while close to a third of patients were also using activities such as massaging feet, soaking or elevating feet. A significant proportion of patients with symptomatic neuropathy experienced a negative impact on the following QOL categories; mobility, usual activities, pain or discomfort and anxiety or depression. Further, those with SDSP were also more likely to be unemployed. Conclusions: Our results show that SDSP is a significant problem affecting patients' QOL and that those patients are not adequately treated for pain, hence seeking alternative management strategies. These strategies do not seem to adequately relieve pain and hence better pain management strategies need to be explored in primary care facilities.